Hypotonlc duodenography. for papilla neoplasms' diagnosis. - Carbó, Alberto (Cirugía del Uruguay, 1987)
The hipotonic duodenography is an ancient radiological diagnostic technique actually seldom used in our center. lt Is a useful procedure In patients with Obstructive jaundlce due to a suspected neoplasm of the choledocoduodenal junction. lis aim indication Is to define the anatomy and ethiology of this disease in those cases in whlch other diagnostic imagenology procedures are not conclusive.